2008
DOI: 10.1163/22941932-90000184
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Pathways in North Temperate Deciduous Broadleaved Trees

Abstract: The interspecific variation of dye ascent in the stems of 44 broadleaved deciduous species growing in Japan was studied using freeze-dried samples after dye injection. The dye ascending pattern differed both within and between ring-porous and diffuse-porous species. In large earlywood vessels of all ring-porous species, the dye ascended only in the outermost annual ring, and the inner annual rings had lost their water transport function. The dye ascending pattern within the inner annual rings in the ring-porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 56 publications
5
38
0
4
Order By: Relevance
“…The latter is needed for scaling-up the sap flow measurements to the stand level. In our study, we considered that the sap flow took place only in the outermost annual ring of black locust, which is supported by the results of dye injection experiments in ring-porous tree species [14,52] and our own dye tracer experiments in living black locust trees (Figure 4). The result showed that only the outermost growth ring was active for xylem flow.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orisupporting
confidence: 53%
“…The latter is needed for scaling-up the sap flow measurements to the stand level. In our study, we considered that the sap flow took place only in the outermost annual ring of black locust, which is supported by the results of dye injection experiments in ring-porous tree species [14,52] and our own dye tracer experiments in living black locust trees (Figure 4). The result showed that only the outermost growth ring was active for xylem flow.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orisupporting
confidence: 53%
“…However, Umebayashi et al (2008) categorized A. sciadophylloides as a ring-porous species, given that its wide vessels are known to transport water mostly during the year in which they are formed, similarly to other ring-porous species.…”
Section: Acanthopanax Sciadophylloides Is Categorized As Semi-ring-pomentioning
confidence: 99%
“…The wide vessels of the pore-zone in ring-porous deciduous species are known to transport water just in the one growing season (Greenidge 1955;Chaney & Kozlowski 1977;Ellmore & Ewers 1986;Utsumi et al 1999;Umebayashi et al 2008), while in diffuse-porous deciduous species vessels in several rings adjacent to the cambium retain their water transport ability for a number of years (Greenidge 1955;Chaney & Kozlowski 1977;Utsumi et al 1998;Umebayashi et al 2008). The time of stem vessel formation relative to leaf appearance is closely related to water distribution pattern within annual sapwood rings in ring-porous and diffuse-porous deciduous species (Ladefoged 1952;Lechowicz 1984;Suzuki et al 1996;Takahashi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the deciduous ring-porous species that have large efficient earlywood vessels, the outermost annual ring has a major role in water transport (Chaney and Kozlowski 1977;Ellmore and Ewers 1986) but the vessels in the inner annual rings do not (Utsumi et al 1996;Umebayashi et al 2008). On the other hand, the diffuseporous species that have many small vessels of about the same sizes maintain their water transport function for many years (Baker and James 1933;Greenidge 1958;Chaney and Kozlowski 1977;Anfodillo et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These species have been categorized into four groups based on their xylem conduit arrangement: semi-ring-porous, diffuseporous, radial-porous, and non-vessel species (Itoh 1995(Itoh , 1996(Itoh , 1997(Itoh , 1998(Itoh , 1999. We obtained an ascending dye pattern using a dye injection method that can show the pathway of dye uptake in xylem at the tissue level (Sano et al 2005;Umebayashi et al 2007Umebayashi et al , 2008. We compared the functional vessel area with the water distribution pattern in each conduit-arrangement category using cryoscanning electron microscopy (cryo-SEM, Utsumi and Sano 2007).…”
Section: Introductionmentioning
confidence: 99%